A study of the status quo and favorable status of succession management deployment from the viewpoint of faculty members at Kermanshah university of medical sciences - Kalhori, Reza Pourmirza; Mousavi, Frank; Laei, Soosan; Shahsavari, Soodeh (International Journal of Engineering and Technology, 2018)
Successful succession management is one of the necessities in any organization, especially universities. In the management of higher education, succession planning deployment requires proprietary methods. Therefore, the present study aimed to investigate the status quo and favorable status of succession management deployment from the viewpoint of faculty members at Kermanshah University of Medical Sciences in 2017. In this descriptive-analytic and cross-sectional study, 95 faculty members were selected from the Departments of Basic Sciences and Clinical Sciences using nonrandom quota sampling. As for data collection, the Kim’s succession planning questionnaire was employed. To analyze data, the SPSS Statistical Software Version 23.0 and the statistical tests of paired t-test, Chi-square and ANOVA were used to compare the status quo of succession management deployment with its favorable status and to study its decisive factors. The results of the present study revealed that there was a significant difference between the status quo and favorable status of t succession management deployment (P<0.0001). The results also demonstrated that there was a significant difference between the status quo of succession management deployment and its favorable status in terms of policy setting, evaluation of candidates, development of candidates, and system evaluation (P<0.001). Moreover, the results indicated that the greatest deployment in the status quo was related to the evaluation of candidates whereas the greatest deployment in the favorable status belonged to policy setting. The findings of the present study demonstrated that there was a clear gap between the status quo and favorable status of succession management deployment from the perspective of faculty members. Hence, it is recommended that qualifications-based selection be employed as the basis on which succession management and talent management can be deployed successfully and effectively at medical universities.